2008
DOI: 10.1111/j.1095-8649.2007.01652.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐direct homing behaviours by adult Chinook salmon in a large, multi‐stock river system

Abstract: Two non-direct homing behaviours, overshoot of natal tributaries and temporary non-natal tributary use, were evaluated for 5150 radio-tagged spring-summer Chinook salmon Oncorhynchus tshawytscha from 40 populations in the large Columbia River system. Over 7 years, 2-44% (mean ¼ 15%) of individuals within each group temporarily entered presumed non-natal tributaries. In addition, many Chinook salmon from lower river tributaries initially travelled 3 to >250 km upstream in the main-stem river beyond confluences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 48 publications
4
62
0
Order By: Relevance
“…Seventh, the occurrence of short distance forays (\2 km) also should be reported, as this indicates active swimming behavior. The timing of these movements may indicate exploration (Keefer et al, 2008), the drive to spawn (Acolas et al, 2004), or a reaction to the environment (Dodson et al, 1972). If possible, these post-tagging movements should be linked to known information about success of spawning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventh, the occurrence of short distance forays (\2 km) also should be reported, as this indicates active swimming behavior. The timing of these movements may indicate exploration (Keefer et al, 2008), the drive to spawn (Acolas et al, 2004), or a reaction to the environment (Dodson et al, 1972). If possible, these post-tagging movements should be linked to known information about success of spawning.…”
Section: Discussionmentioning
confidence: 99%
“…Often the downstream movements of upstream migrating salmon are described as a purposeful behavior in response to the environment, obstacles, or a mechanism of homing . These complex behaviors include overshooting of natal systems (Naughton et al, 2006), exploratory movements (Keefer et al, 2008), seeking alternate routes, waiting for appropriate conditions (Thorstad et al, 2005;Holbrook et al, 2009), disorientation in certain hydraulic conditions (Naughton et al, 2006), being swept over dams (Matter & Sandford, 2003), or varying sensitivity in distinct migratory phases (Makinen et al, 2000;Jokikokko, 2002). Aberrant movement in salmonids has not been explicitly related to ''fallback'' or tag effect (Young et al, 2006); for example, when radio tags were used to examine the effect of catch-and-release on adult Atlantic salmon (Salmo salar), uncharacteristic up and downstream movements of radiotagged fish observed post-release were attributed to angling (Thorstad et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…As such, we can address the issue of straying, but must define strays as individuals not from these hatcheries; that is, individuals who were found in Conneaut Creek, but were not Ohio-or Pennsylvania-stocked fish. We found that 13.8% of adult (non-yearling) steelhead trout collected in Conneaut Creek were known strays (stocked by Michigan and New York), which is higher than the 2.5% of knownorigin salmonids that were considered permanent strays in the Columbia and Snake Rivers (Keefer et al, 2008). However, this is not unprecedented for populations of stocked fish.…”
Section: Tablementioning
confidence: 96%
“…Radiotelemetry data also allowed estimation of salmon fallback at dams. If unmeasured, fish that fall back and do not reascend can produce overestimates of upstream escapement (Dauble and Mueller, 2000;Boggs et al, 2004) and underestimates of escapement to downstream sites (Keefer et al, 2008). The PITtag detection data currently collected at dams cannot account for most fallback fish that do not reascend fishways .…”
Section: Monitoring System Tradeoffsmentioning
confidence: 99%